PERANAN PEMBELAJARAN DARING KELAS III SD FREE METHODIST-2 - Dewi Ulina Ginting; Rumiris Lumban Gaol; Dyan Wulan Sari HS; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the role of online learning for grade III students of SD Free Methodist 2 Medan in the academic year 2020/2021. This research was descriptive qualitative research, with the subjects being third-grade students of SD Free Methodist 2 Medan. Data were collected through observation, interviews, and documentation. Based on the research results, it was concluded that online learning was effectively carried out during the pandemic to break the transmission of the coronavirus. It was suggested that teachers create complete modules so that students would not need to search for answers on Google and could instead refer to their notes. During this period, teachers should actively engage with students, such as through video calls, rather than only sending assignments via WhatsApp groups. The results also indicated that online learning helped anticipate student boredom, as students better understood the material when explained directly by teachers, while in many cases, parents assisted in explaining the material.